Challenge to Unity: Relationship Between Hemispheric Asymmetry of the Default Mode Network and Mind Wandering. (21st April 2018) - Kajimura, Shogo; Kochiyama, Takanori; Abe, Nobuhito; Nomura, Michio
Abstract: The default mode network (DMN) is considered a unified core brain function for generating subjective mental experiences, such as mind wandering. We propose a novel cognitive framework for understanding the unity of the DMN from the perspective of hemispheric asymmetry. Using transcranial direct current stimulation (tDCS), effective connectivity estimation, and machine learning, we show that the bilateral angular gyri (AG), which are core regions of the DMN, exhibit heterogeneity in both inherent network organization and mind wandering regulation. Inherent heterogeneities are present between the right and left AG regarding not only effective connectivity, but also mind wandering regulation; the right AG is related to mind-wandering reduction, whereas the left AG is related to mind-wandering generation. Further supporting this observation, we found that only anodal tDCS of the right AG induced machine learning-detectable changes in effective connectivity and regional amplitude, which could possibly be linked to reduced mind wandering. Our findings highlight the importance of hemispheric asymmetry to further understand the function of the DMN and contribute to the emerging neural model of mind wandering, which is necessary to understand the nature of the human mind.